Pulmonary effects of immediate versus deferred antiretroviral therapy in HIV-positive individuals: a nested substudy within the multicentre, international, randomised, controlled Strategic Timing of Antiretroviral Treatment (START) trial. Issue 12 (December 2016) - Kunisaki, Ken M; Niewoehner, Dennis E; Collins, Gary; Aagaard, Bitten; Atako, Nafisah B; Bakowska, Elzbieta; Clarke, Amanda; Corbelli, Giulio Maria; Ekong, Ernest; Emery, Sean; Finley, Elizabeth B; Florence, Eric; et al.
Summary: Background: Observational data have been conflicted regarding the potential role of HIV antiretroviral therapy (ART) as a causative factor for, or protective factor against, COPD. We therefore aimed to investigate the effect of immediate versus deferred ART on decline in lung function in HIV-positive individuals. Methods: We did a nested substudy within the randomised, controlled Strategic Timing of Antiretroviral Treatment (START) trial at 80 sites in multiple settings in 20 high-income and low-to-middle-income countries. Participants were HIV-1 infected individuals aged at least 25 years, naive to ART, with CD4 T-cell counts of more than 500 per μL, not receiving treatment for asthma, and without recent respiratory infections (baseline COPD was not an exclusion criterion). Participants were randomly assigned to receive ART (an approved drug combination derived from US Department of Health and Human Services guidelines) either immediately, or deferred until CD4 T-cell counts decreased to 350 per μL or AIDS developed. The randomisation was determined by participation in the parent START study, and was not specific to the substudy. Because of the nature of our study, site investigators and participants were not masked to the treatment group assignment; however, the assessors who reviewed the outcomes were masked to the treatment group. The primary outcome was the annual rate of decline in lung function, expressed as the FEV1 slope in mL/year; spirometry was done annually during follow-up for up to 5 years. We analysed data on an intention-to-treat basis, and planned separate analyses in smokers and non-smokers because of the known effects of smoking on FEV1 decline. The substudy was registered atClinicalTrials.gov numberNCT01797367 . Findings: Between March 11, 2010, and Aug 23, 2013, we enrolled 1026 participants to our substudy, who were then randomly assigned to either immediate (n=518) or deferred (n=508) ART. Median baseline characteristics included age 36 years (IQR 30–44), CD4 T-cell count 648 per μL (583–767), and HIV plasma viral load 4·2 log10 copies per mL (3·5–4·7). 29% were female and 28% were current smokers. Median follow-up time was 2·0 years (IQR 1·9–3·0). We noted no differences in FEV1 slopes between the immediate and deferred ART groups either in smokers (difference of −3·3 mL/year, 95% CI −38·8 to 32·2; p=0·86) or in non-smokers (difference of −5·6 mL/year, −29·4 to 18·3; p=0·65) or in pooled analyses adjusted for smoking status at each study visit (difference of −5·2 mL/year, −25·1 to 14·6; p=0·61). Interpretation: The timing of ART initiation has no major short-term effect on rate of lung function decline in HIV-positive individuals who are naive to ART, with CD4 T-cell counts of more than 500 per μL. In light of updated WHO recommendations that all HIV-positive individuals should be treated with ART, regardless of their CD4 T-cell count, our results suggest an absence of significant pulmonary harm with such an approach. Funding: US National Heart Lung and Blood Institute, US National Institute of Allergy and Infectious Diseases, Division of AIDS, Agence Nationale de Recherches sur le SIDA et les Hipatites Virales (France), Australian National Health and Medical Research Council, Danish National Research Foundation, European AIDS Treatment Network, German Ministry of Education and Research, UK Medical Research Council and National Institute for Health Research, and US Veterans Health Administration Office of Research and Development.